Long-term antimicrobial effect of polylactide-based composites suitable for biomedical use. (December 2022) - Škrlová, Kateřina; Rybková, Zuzana; Stachurová, Tereza; Zagora, Jakub; Malachová, Kateřina; Měřinská, Dagmar; Gabor, Roman; Havlíček, Miroslav; Muñoz-Bonilla, Alexandra; Fernández-García, Marta; Plachá, Daniela
Abstract: This work deals with the preparation and characterization of antimicrobial polymeric composite materials based on polylactide, which is currently widely investigated to produce temporary implants. Polylactide was blended with antimicrobial fillers: silver, hexadecylpyridinium or hexadecyltrimethylammonium bromides anchored on vermiculite or graphene oxide matrices in an amount of 1% wt. The prepared samples were characterized by conventional methods, further they were exposed to degradation tests in physiological saline conditions and characterized for their antimicrobial properties using common pathogen microorganisms. It has been proven that the prepared polylactide composites change their antimicrobial effects after being in physiological saline of pH 7 and 9 for 0–6 months. The weight of the composites changed by about 10%, and antimicrobial properties were growing over time. The effectiveness of the composites was confirmed for 6 months at minimum. Therefore, they are suitable for the preparation of temporary stents, catheters or implants suitable for fracture fixation. Graphical abstract: Image 1 Highlights: Polylactide-based composites with proven antimicrobial properties were prepared. Long-term antimicrobial activity was proven for 6 months. Antimicrobial effectiveness was determined for environments with pH 7 and 9. Filler containing hexadecylpyridinium was efficient against Candida albicans . Materials are suitable for biomedical applications.